The genetic code: HRM internal integration scale. (21st November 2016) - Kidron, Aviv; Tzafrir, Shay S.; Meshoulam, Ilan
Abstract : Purpose: The purpose of this paper is to present a scale for measuring internal integration within human resource management (HRM) departments, which is developed and validated in this paper. Thus far, no valid, comprehensive operational instrument for measuring HRM internal integration has been introduced in the literature. Design/methodology/approach: The scale items were developed on the basis of a qualitative analysis. The authors recruited 233 HRM professionals from 29 organizations to participate in the survey. In this paper, the authors present evidence of content validity, internal consistency reliability and construct validity that provides support for the use of an HRM internal integration scale. Exploratory factor analysis was conducted to determine the underlying factors that comprise HRM internal integration, while confirmatory factor analysis was used as a confirmatory test of the scale. Findings: The results of this study led to the development of a standardized 34-item instrument that can be used for measuring HRM internal integration. Originality/value: The use of the scale opens up a new research avenue by focusing on the nature of integration processes, particularly within HRM systems. The scale will allow studies to be compared across various contexts.